Transitioning to nutrition-sensitive food environments in Ghana: Triple sector strategies to reduce the triple burden of malnutrition - Mockshell, Jonathan; Asante-Addo, Collins; Andam, Kwaw S.; Asante, Felix Ankomah (International Food Policy Research Institute, 2021)
The triple burden of malnutrition is growing in low- and middle-income countries (LMICs). Increasing access to affordable ultra-processed foods in the food environment is contributing to this problem. While existing explanations for this triple burden of malnutrition have examined demand-side factors of food choices, the supply-side policies relating to the food environment drivers, ideas and actors’ interests have been neglected. Using a case study of Ghana, this analysis combines the Advocacy Coalition Framework with the narrative analysis to unpack the supply-side food environment policies and actors driving the triple burden of malnutrition. Applying a mixed methods analysis of the transcripts, the narratives reveal public, private and civil society organization (CSO) coalitions with different ideas and interests in the food environment. In the private sector coalition, food companies engage in aggressive advertising and are driven by profit motives – leading to the supply of more ultra-processed foods. The public sector is failing to regulate the market because of inadequate policies, limited institutional capacities and coordination, enforcement challenges, inadequate resources, and self-interest. Social activism by CSOs, for example, pressuring food companies to deliver healthy foods and holding the government accountable, is also lacking. The result is a triple sector (public, private and CSO) failure in the urban food environment with consequences on the availability of ultra-processed foods. This has long-lasting implications for the reduction of the triple burden of malnutrition and the achievement of zero hunger. To accelerate nutrition-sensitive food environments that deliver healthier food options, we argue that it is critical to entertain the ideas and interests of stakeholders and implement food environment policies that cover private and public sector initiatives, as well as increase consumer awareness.